The effect of beach volleyball training on running economy and VO2max of indoor volleyball players - Balasas, D.; Vamvakoudis, E.; Christoulas, K.; Stefanidis, P.; Prantsidis, P.; Papaevangelou, E. (Journal of Physical Education and Sport, 2013)
The purpose of this study was to investigate the effect of systematic beach volleyball training and competition on running economy (RE) and VO2max of indoor volleyball players. Thus, the participants underwent two measurements. The first measurement (PRE) occurred before the players begin systematic beach volleyball training, just after the end of indoor volleyball season. The second measurement (POST) occurred after the final tournament of the beach volleyball season, twelve weeks after the first measurement. All of them underwent anthropometric measurements, body fat assessment and performed running on treadmill at speeds of 8, 10 and 12km/h for three minutes at each level. Parameters such as heart rate (HR), VO2 in absolute and relative values, respiratory exchange ratio (RER) and minute ventilation (VE) were recorded. Moreover, VO2max was also tested. Body mass and fat were significantly decreased after the beach volleyball period. HR decreased significantly (p<.01) at 8, 12 and 10 km/h and VO2 differ significantly, with a decrease in 8 (p<.05) 10 (p<.01) and 12 km/h (p<.001) in both absolute (l/min) and relative (ml/kg/min) values, showing an improvement of RE. RER decreased significantly at the speeds of 10 (p<.05) and 12 km/h 1 (p<.01), whereas VE recorded a significant difference in 12 km/h (p<.001). Additionally, the results indicate a significant increase in VO2max (p<.01) both in absolute (l/min) and relative (ml/kg/min) values. Conclusively, it seems that systematic beach volleyball training leads to an improvement of RE and VO2max of the amateur indoor volleyball players. These findings indicate that the improvements caused by beach volleyball training can be considerably effective in the performance of the athletes throughout the total duration of a volleyball game.